2015
DOI: 10.1124/mol.115.099176
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Basis of Attenuated Inverse Agonism of Angiotensin II Type 1 Receptor Blockers for Active-State Angiotensin II Type 1 Receptor

Abstract: Ligand-independent signaling by the angiotensin II type 1 receptor (AT1R) can be activated in clinical settings by mechanical stretch and autoantibodies as well as receptor mutations. Transition of the AT1R to the activated state is known to lower inverse agonistic efficacy of clinically used AT1R blockers (ARBs). The structure-function basis for reduced efficacy of inverse agonists is a fundamental aspect that has been understudied not only in relation to the AT1R but also regarding other homologous receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 47 publications
4
58
0
Order By: Relevance
“…We recently analyzed the structure-function relationships of losartan, EXP3174 (an active metabolite of losartan), valsartan and irbesartan for the basal and constitutively active states of AT1R, and identified the molecular mechanism of decreased maximal inverse agonist activity of the ARBs for the active state of AT1R compared to the ground state [16]. Details of the mechanism are described in Sections 3 through 5.…”
Section: Structural Classification Of Arbsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently analyzed the structure-function relationships of losartan, EXP3174 (an active metabolite of losartan), valsartan and irbesartan for the basal and constitutively active states of AT1R, and identified the molecular mechanism of decreased maximal inverse agonist activity of the ARBs for the active state of AT1R compared to the ground state [16]. Details of the mechanism are described in Sections 3 through 5.…”
Section: Structural Classification Of Arbsmentioning
confidence: 99%
“…This landmark achievement paved the way for determination of the precise docking models of various ARBs based on the solved crystal structure [16, 43]. Energy-based docking simulations of the ARBs using the crystal structure of human AT1R revealed that the interactions of the biphenyl-tetrazole ARBs with AT1R were completely different from previously proposed ARB-AT1R interactions [16, 43, 44]. For example, differences of losartan binding mode between in a previously proposed AT1R model based on bovine rhodopsin structure and crystal structure of human AT1R are shown in Fig.…”
Section: Crystal Structure Of At1r Provides Precise Ligand-receptomentioning
confidence: 99%
See 2 more Smart Citations
“…Angiotensin receptor included in this system is a hypertension-related G protein-coupled receptor (GPCR) [21]. There are two main types: AT1 and angiotensin II type-2 receptor (AT2), among which the former receives the most research [22].…”
Section: Introductionmentioning
confidence: 99%